Optimalization Of Village Funds For Community Economic Development (Case Study in Sungai Awan Kiri Village) - Agustinus Beni Tridianto; Muhammad Nur Abdi (International Journal of Economics, Business and Innovation Research, 2024)
This research was conducted to see how village funds can be used optimally in development in Sungai Awan Kiri Muara Pawan Ketapang village and its utilization to support community empowerment. This research uses descriptive methods and is conducted through a qualitative model. The data collection method used is direct observation and in-depth interviews with the focus of the research objectives that the researcher wants to achieve. The informants used in this study consisted of 4 (four) people consisting of the Village Head, Village Secretary, Finance Section and Community Leaders. The analysis method used is data collection, data reduction, data presentation, and conclusion drawing. The results of the study found that Sungai Awan Kiri Village succeeded in empowering the community's economy through the Village Fund. Sungai Awan Village focuses on the existing village potential, involves active communities, and establishes cooperation with the private sector so that community income increases and the village becomes more advanced. This case study can be emulated by other villages to achieve sustainable village development.